3(x+2)-2x+4=x+6

Simple and best practice solution for 3(x+2)-2x+4=x+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x+2)-2x+4=x+6 equation:


3(x+2)-2x+4=x+6

We simplify the equation to the form, which is simple to understand
3(x+2)-2x+4=x+6

Reorder the terms in parentheses
+(+3x+6)-2x+4=x+6

Remove unnecessary parentheses
+3x+6-2x+4=+x+6

We move all terms containing x to the left and all other terms to the right.
+3x-2x-1x=+6-6-4

We simplify left and right side of the equation.
0x=-4

0=-4

The left and right sides are not equal, therefore there is no solution. This equation is invalid.

See similar equations:

| 12+8.2x=12 | | 4.1(3+2x)-.3=12 | | 3.3x-4.14=6.519 | | 4y+5=14+y | | 18+6(9-3)= | | 1/3(x+1)=2/3(x) | | (x+2)-2(3-3x)=3(x+4)-4 | | 79080000000/10 | | 9x+273=-7x+168 | | -6(v+2)+3v+7=8v+7 | | 3x^2-14x+6=0 | | 3/5x+(-3x/2) | | 11-4x=11x+2 | | 1/5y=8 | | -19=x+(-9) | | -4x+3=-5x+4 | | -1/6/8/7 | | 4(x^9)-4x=0 | | 25=(16/19)x+1 | | 24=(16/19)x+1 | | 23=(16/19)x+1 | | 22=(16/19)x+1 | | 4(x^3)-4y=0 | | 21=(16/19)x+1 | | 20=(16/19)x+1 | | 19=(16/19)x+1 | | 18=(16/19)x+1 | | 17=(16/19)x+1 | | 1x-5+4x-2=8x | | 16=(16/19)x+1 | | 15=(16/19)x+1 | | 1.21=11(0.51+0.4x) |

Equations solver categories